Tailoring Zeolite-Supported Bifunctional Cobalt Catalysts for Direct Conversion of Syngas to Liquid Fuels - Lim, Jae Jun; Park, Seon-Ju; Yun, Yang Sik; Lee, Kwan-Young; Lee, Yun-Jo; Han, Seung Ju (American Chemical Society, 2025)
The Fischer–Tropsch synthesis (FTS) is a promising method for converting syngas (H2/CO) into valuable liquid fuels, such as gasoline, diesel, and jet fuel. However, low-temperature FTS over cobalt-based catalysts exhibits high selectivity for heavier hydrocarbons, which have relatively limited market demand. As a result, an additional hydrotreatment step, such as hydrocracking, is needed to break them down into lighter, more practical liquid fuels, adding complexity and cost to the overall production. In this study, we investigated a single-stage syngas-to-liquid fuel process using zeolite-supported bifunctional cobalt catalysts. The catalysts were systematically tailored and optimized through zirconia modification, ruthenium doping, and the introduction of a mesoporous structure. The resulting bifunctional catalysts showed deviations in the Anderson–Schulz–Flory (ASF) distribution, indicating the acid-catalyzed cracking functions of the zeolite support. Ruthenium doping mainly enhanced the dispersion and reducibility of cobalt, boosting the FTS performance. In addition, zirconia modification stabilizes the cobalt active sites by forming Co–Zr interfaces, especially for mesoporous zeolite-supported catalysts. Meanwhile, mesoporous H-ZSM-5 alleviates the diffusion limitations by providing expanded pore openings, which facilitates the hydrocracking and isomerization of heavy hydrocarbons produced from FTS. Among the catalysts, CoRu/Zr/meso-H-ZSM-5 showed the highest CO conversion (69.7%) and the highest C5–20 hydrocarbons productivity (0.58 gHCs·gcat–1·h–1) at 230 °C and 2.0 MPa with enhanced long-term stability over a 500 h reaction. The key strategy of the zeolite-supported hybrid cobalt catalysts lies in achieving a stable and highly dispersed cobalt active phase while preserving the acidic properties of the zeolite. This approach demonstrates the potential of tailored bifunctional catalysts for the efficient and selective production of liquid fuels via FTS.